Survey of Staphylococcus aureus carriage by free‐living red deer (Cervus elaphus): Evidence of human and domestic animal lineages. Issue 5 (22nd March 2022) - Luzzago, Camilla; Lauzi, Stefania; Ehricht, Ralf; Monecke, Stefan; Corlatti, Luca; Pedrotti, Luca; Piccinini, Renata
Abstract: Staphylococcus aureus is a pathogen that can affect multiple host species. Evidence of transmission between humans and animals and among different animal species has been reported in recent years. In this study, we investigated 284 free‐living red deer ( Cervus elaphus ) in the Central Italian Alps to assess the prevalence and molecular characteristics of S. aureus in nasal and intestinal samples in relation to host features and environmental factors. A prevalence of 90%, 26.2% and 10.7% of S. aureus was detected in nasal rectal swabs and faeces, respectively. Calves had a higher probability of being S. aureus intestinal carriers than adults, especially in females when considering faecal samples. Clonal complex (CC) 425 was the most prevalent lineage (61.5%). This is a lineage known to be widespread in both domestic and free‐living animals. It was followed by CC2671 (15.4%) and CC350 (6.4%). A high rate of the phage‐borne virulence factor lukM/lukF‐P83 was detected in CC425 and CC350. Further lineages, which are known to occur in both humans and animals, were detected sporadically in red deer faeces only, that is, CC7, CC9, CC121 and CC707, harbouring the genes of the penicillinase operon and a gene for macrolide resistance (CC9 and CC121). Methicillin resistance genes mec A and mec C were not found. Our results suggest that free‐living red deer may be reservoir for S. aureus in Alpine habitats.